3(a - 3) = 2(a + 4) solve

Rating

0

3(a - 3) = 2(a + 4);

3a - 9 = 2a + 8;

a = 17;

3a - 9 = 2a + 8;

a = 17;

Added 12/21/2014 10:02:53 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [12/21/2014 11:40:45 AM]

8y - 3 = 5(y - 1) + 3y solve for y **Weegy:** 8y(y - 4) + 3y(y + 2) = 8y^2 - 32y + 3y^2 + 6y; = 11y^2 - 26y (More)

Question|Asked by devyn

Updated 12/21/2014 11:40:26 AM

1 Answer/Comment

8y - 3 = 5(y - 1) + 3y;

8y - 3 = 5y - 5 + 3y;

8y - 3 = 8y - 5;

8y - 8y = -5 + 3;

0 = -2;

No solutions exist.

8y - 3 = 5y - 5 + 3y;

8y - 3 = 8y - 5;

8y - 8y = -5 + 3;

0 = -2;

No solutions exist.

Added 12/21/2014 11:40:26 AM

This answer has been confirmed as correct and helpful.

29,298,598

questions answered

There are no comments.